Multifocal motor neuropathy with conduction block: a study of 24 patients. Issue 1 (July 1995) - Bouche, P; Moulonguet, A; Younes-Chennoufi, A B; Adams, D; Baumann, N; Meininger, V; Léger, J M; Said, G
Abstract : Twenty four patients with pure motor neuropathy are reported. The chronic motor involvement associated with fasciculations and cramps, mainly in the arms, led, in most patients, to an initial diagnosis of motor neuron disease. In some patients (nine of 24), there was no appreciable muscle atrophy. Tendon reflexes were often absent or weak. The finding of persistent multifocal conduction block confined to motor nerve fibres raises questions about the nature and the importance of this syndrome. Segmental reduction of motor conduction velocity occurred at the site of the block, but significant slowing of motor nerve conduction was not found outside this site. The response to intravenous IVIg treatment seems to be correlated with the absence of amyotrophy. Patients with little or no amyotrophy had an initial and sustained response to IVIg, and did not develop amyotrophy during the follow up study. They could be considered to have a variant of chronic inflammatory demyelinating polyneuropathy. Patients with pronounced amyotrophy independent of the disease duration did not respond as well to IVIg treatment, suggesting the existence of a distinct entity. Among the patients treated about two thirds who had an initial good response to IVIg had high or significant antiganglioside GM1 (anti-GM1) antibody titres, but there was no correlation between the high titres before treatment and long lasting response to IVIg treatment.